Nursed in the desert - Khan , S (Goodword kidz : India, 2010)
Nursed in the Desert by Saniyasnain Khan is a children's book that introduces young readers to the early life of Prophet Muhammad (PBUH). The story focuses on his infancy and early childhood, particularly highlighting the practice of sending infants to the desert to be nursed by Bedouin women, a tradition that was believed to promote health and strength